Brazilian autonomy in the quest for United Nations Security Council reform - Mariana Pimenta Oliveira Baccarini; Pascoal Teófilo Carvalho Gonçalves (Revista Brasileira de Política Internacional, 2025)
Abstract This article aims to analyze Brazil’s search for UNSC reform from the debate on autonomy in the formulation and performance of Brazilian foreign policy. To this end, we analyzed more than 6,000 presidential speeches between 1985 and 2022, to identify the approach of each of the governments and the strategy of rapprochement of the countries by the Brazilian presidents. We show that, although the issue has been constantly mentioned on the country’s foreign policy agenda, in practice, it was a more incisive policy in the first two terms of the Lula government.